Effect of Panavir on Herpes simplex Virus Types 1 and 2 Proteins Synthesis in Cell Culture - R. R. Klimova; A. A. Kushch; N. E. Fedorova; A. A. Litvin (Антибиотики и Химиотерапия)
The effect of Panavir on the synthesis of ultraearly (α), early (β) and late (γ) proteins of Herpes simplex virus types 1 and 2 in the culture of Vero cells was studied. It was shown that the level of the proteins suppression depended on the infection multiplicity and the time of the Panavir addition to the culture.